2007
DOI: 10.1080/02705060.2007.9664149
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Responses to Darkness betweenMicrocystis aeruginosaandChlorella pyrenoidosa

Abstract: The effect of darkness on the cyanobacterium Microcystis aeruginosa and the green alga Chlorella pyrenoidosa were observed. Cell growth, metabolic activity, chlorophyll a fluorescence, cell size, and maximum quantum yield (F, : F,) were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
3
6
1
Order By: Relevance
“…Similar result was reported by Zhang et al (2007) who found that Microcystis was more capable of withstanding the dark circumstances. Furusato et al (2004) found that the cell numbers of M. aeruginosa decreased markedly after more than 7 days of darkness and the abundance of S. quadricauda was not affected during 20 days of darkness.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar result was reported by Zhang et al (2007) who found that Microcystis was more capable of withstanding the dark circumstances. Furusato et al (2004) found that the cell numbers of M. aeruginosa decreased markedly after more than 7 days of darkness and the abundance of S. quadricauda was not affected during 20 days of darkness.…”
Section: Discussionsupporting
confidence: 90%
“…However, the cell number and Chl a content of S. quadricauda decreased significantly. Similar result was also found in Chlorella pyrenodosa after darkness (Zhang et al, 2007). Compared to colonial Microcystis, the cell number of unicellular Microcystis had a significant decrease, suggesting that colonial Microcystis can survive a longer period under the stress of darkness and low temperature than unicellular Microcystis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Whereas some species of marine phytoplankton adapt to the dark by reducing their metabolism to a lower level of activity (type I cells), other species maintain unchanged metabolic activity (type II) (Jochem, 1999). As has been suggested by other authors (Zhang et al, 2007;Wu et al, 2008) and confirmed by our study, M. aeruginosa can be included in the former group, since its metabolic activity (measured as fluorescein fluorescence after FDA hydrolysis) decreases in darkness. The results of our study also proved that the addition of H 2 O 2 to cyanobacterial cell suspensions can inhibit metabolic activity regardless of the experimental regime.…”
Section: Discussionsupporting
confidence: 76%